2015
DOI: 10.1164/rccm.201411-2099ci
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Intensive Care Unit

Abstract: Sleep is an important physiologic process, and lack of sleep is associated with a host of adverse outcomes. Basic and clinical research has documented the important role circadian rhythm plays in biologic function. Critical illness is a time of extreme vulnerability for patients, and the important role sleep may play in recovery for intensive care unit (ICU) patients is just beginning to be explored. This concise clinical review focuses on the current state of research examining sleep in critical illness. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
278
0
41

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(322 citation statements)
references
References 96 publications
(98 reference statements)
3
278
0
41
Order By: Relevance
“…Patients admitted to the intensive care unit (ICU), who are usually critically ill patients, need more sleep, however, they are at a higher risk for sleep deprivation, poor sleep quality, and disturbed sleep-wake cycle (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Patients admitted to the intensive care unit (ICU), who are usually critically ill patients, need more sleep, however, they are at a higher risk for sleep deprivation, poor sleep quality, and disturbed sleep-wake cycle (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Reported common circadian rhythm, producing negative impacts on cardiovascular and physiological function. 7,14 The World Health Organization (WHO) guidelines recommend that the average sound levels in hospital should not exceed 30 dB(A) during the day or night, and night-time peak levels should not exceed 40 dB(A). 14 However, studies in specific countries have reported sound levels in ICUs that exceed these recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problems exacerbate the healing process during hospitalization and can endure beyond hospitalization. [1][2][3] Researchers in one study 4 documented that sleep difficulties may endure beyond hospitalization: 50% of respondents reported moderate to severe sleep problems 1 week after discharge. Other studies have offered evidence that sleep problems experienced during hospitalization increase the risk for development of chronic insomnia.…”
mentioning
confidence: 99%
“…6,7 Other sleep disruption factors include lighting that interferes with sleep-wake cycles, pain, anxiety, and symptoms related to patients' underlying illness. 4 Many of these sleep-disrupting factors are amplified in intensive care units.…”
mentioning
confidence: 99%